2020
DOI: 10.3390/ijerph17020644
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic and Anti-Fouling Performance of Surface on Parabolic Morphology

Abstract: The hydrophobicity and anti-fouling properties of materials have important application value in industrial and agricultural production and people's daily life. To study the relationship between the unit width L 0 of the parabolic hydrophobic material and the hydrophobicity and anti-fouling properties, the rough surface structure of the parabolic with different widths was prepared by grinding with different SiC sandpapers, and further, to obtain hydrophobic materials through chemical oxidation and chemical etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…7 and Movie S6. † 19 When applied, the polymer-coated sponge composite and membrane were unable to maintain the self-cleaning nature. The self-cleaning nature of the above composite and membrane avoids the adhesion of any nutrient or soil material that could help them develop fouling.…”
Section: Structural Descriptionmentioning
confidence: 99%
“…7 and Movie S6. † 19 When applied, the polymer-coated sponge composite and membrane were unable to maintain the self-cleaning nature. The self-cleaning nature of the above composite and membrane avoids the adhesion of any nutrient or soil material that could help them develop fouling.…”
Section: Structural Descriptionmentioning
confidence: 99%
“…When the experiment was repeated with only PP fabric, the mass of 65 mg of PP fabric increased to 662 mg due the absorption of soilrhodamine-B suspension (Figure S47). 70 The above experiments showed that the SHMOF−PP composite has both selfcleaning as well as an anti-fouling nature. The microorganism present in the water body requires water for their growth.…”
Section: Durability Of Shmof−pp Composite In Differentmentioning
confidence: 82%
“…As shown in Table 1, the reference materials copper and Al exhibited a slight hydrophobicity of their surface (around [78][79][80][81][82][83][84][85], in accordance with previously published data. [48][49][50][51] In contrast, the anodization process on Al signicantly decreased the contact angle (around 49 ), the AA being more hydrophilic than Al (p < 0.001). These results are in contradiction with the hydrophobic/superhydrophobic properties normally induced by the hard anodization process of aluminum materials.…”
Section: Surface Characterizationmentioning
confidence: 96%